The Efforts to Improve Adolescent’s Self-Resilience in Facing The Risk of Teenager Sexual Behavior - Eva Nurlina Aprilia (Universitas Pendidikan Indonesia, 2022)
The large proportion of adolescent population leads teenagers into groups at risk and vulnerable to health problems, namely smoking, alcohol consumption, drug consumption, depression or risk of suicide, emotional, physical problems, school problems, and sexual behavior. Based on this case, health promotion needs to be carried out through counseling or health education regarding efforts to improve adolescents’ self-resilience in facing adolescent problems. This research was conducted by providing training in the form of pre-test, role play, and post-test. The research subjects consisted of 19 adolescents with the characteristics of the respondents consisted of age, occupation, knowledge, and attitude. The research result showed that knowledge of the adolescents after receiving counseling and training regarding to efforts to improve adolescent self-resilience in facing the risks of teenager sexual behavior increased to 5.26% (from 26.31% pre-test results and post-test results to 31.57 %). Meanwhile, the attitude towardfamily awareness increased to 10.52% from the results of the pre-test which were not in the good category, and the results of the post-test to 10.52%). The conclusion from the research results was that there was an improvement in knowledge and attitude, both before and after counseling and training actions which were carried out regarding the efforts to improve adolescent self-resilience in facing the Risks of teenage Sexual Behavior.